Integration of small-scale mohair farmers into the commercial agricultural economy in Lesotho: a new institutional economics approach - Rantlo, Montoeli Ashby (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2018)
Agriculture continues to be a strategic sector in the development of most low-income countries like Lesotho where small-scale farming is the dominant livelihood activity that provides income and employment to the people. Smallholder farmers' integration into the commercial agricultural markets is a crucial element for economic development and has become a part of development strategies for developing countries and the objectives of international development institutions. The integration of the smallholders into these markets is dependent upon a number of factors including formal and informal institutions. Factors like population growth and demographic changes, technological change and introduction of new commodities, development of infrastructure and market institutions, development of the nonfarm sector and broader economy, rising labour opportunity costs, and macroeconomic, trade and sectoral policies affecting prices and other driving forces determine market participation. In addition, development of input and output markets, institutions like property rights and land tenure, market regulations, cultural and social factors affecting consumption preferences, production and market opportunities and constraints, agro-climatic conditions, and production and market related risks are other factors that affect the commercialisation process. On the other hand, factors like smallholder resource endowments including land and other natural capital, labour, physical capital, and human capital among others are household specific and considered internal determinants of market participation. Nevertheless, the decision to participate in agricultural markets lies with the individual farming household. Under the New Institutional Economics (NIE), this decision is influenced by institutional factors such as risk and preferences, factors which affect household production and the level of costs associated with market transactions. These market transactions are commonly referred to as transaction costs. The study focused on investigating the institutions that limit the integration of small-scale mohair farmers into the commercial agricultural economy in Lesotho. The documentation and evaluation of the institutional structure of the mohair industry is performed whereby the institutional factors influencing participation of small-scale mohair farmers in formal, informal and illegal markets in Lesotho and factors contributing to transaction costs associated with the integration of small-scale farmers into the commercial mohair sector are investigated. Therefore, the investigation will help to address the institutional problems hindering the development of an effective marketing structure for the commercialisation of small-scale mohair producers in Lesotho. The results of the study show that the small-scale mohair farmers that use the formal markets are integrated into the commercial agricultural economy and these farmers' integration into the mainstream economy is influenced by access to government support in the form of shearing sheds, transport subsidies and advisory services. They also have access to market information, marketing infrastructure, knowledge of grades and standards and secure property rights. Other factors that helped their integration into the commercial economy is their contractual agreements with mohair buyers, path dependent based decision making as well as the collective approach to mohair farming. The small-scale mohair farmers using the informal markets do not receive the advantages received by the famers in the formal markets. These small-scale mohair farmers are not integrated into the commercial markets and their only option is the informal markets and their participation in these markets is enhanced by their marketing arrangements with the informal traders, culture influenced decisions, social capital and prompt payments. Despite integration into the commercial agricultural economy, small-scale farmers that use formal markets face the challenges of power imbalances, mistrust and conflicts which may affect this integration into the commercial markets if left unchecked. The study concludes that in the face of institutional challenges, the small-scale mohair farmers using the formal markets are integrated into the commercial agricultural economy and there is potential for improvement of their integration as well as the integration of the small-scale mohair farmers that use the informal markets if institutional challenges are addressed.
Keywords: Farms, Small -- Lesotho; Mohair -- Lesotho; Institutional economics; Transaction costs; Informal sector (Economics)